Integrated weed management using planting pattern, cultivar, and herbicide in dry-seeded rice in northwest India - Mahajan, Gulshan; Poonia, Vikas; Chauhan, Bhagirath S. (Cambridge University Press, 2014)
Field experiments were conducted in Punjab, India, in 2011 and 2012 to study the integrated effect of planting pattern [uniform rows (20-cm spacing) and paired rows (15-, 25-, and 15-cm spacing)], cultivars (PR-115 and IET-21214), and weed control treatments (nontreated control, pendimethalin 750 g ai ha−1, bispyribac-sodium 25 g ai ha−1, and pendimethalin 750 g ha−1 followed by bispyribac-sodium 25 g ha−1) on weed suppression and rice grain yield in dry-seeded rice. In the nontreated control, IET-21214 had higher grain yield than PR-115 in both planting patterns. However, such differences were not observed within the herbicide treatment. IET-21214 in paired rows, even in nontreated control, provided grain yield (4.7 t ha−1) similar to that in uniform rows coupled with the sole application of pendimethalin (4.3 t ha−1) and bispyribac-sodium (5.0 t ha−1). In uniform rows, sequential application of pendimethalin (PRE) and bispyribac-sodium (POST) provided the highest grain yield among all the weed control treatments and this treatment produced grain yield of 5.9 and 6.1 t ha−1 for PR-115 and IET-21214, respectively. Similarly, in paired rows, PR-115 in paired rows treated with sequential application of pendimethalin and bispyribac-sodium had highest grain yield (6.1 t ha−1) among all the weed control treatments. However, IET-21214 with the sole application of bispyribac-sodium produced grain yield similar to the sequential application of pendimethalin and bispyribac-sodium. At 30 days after sowing, PR-115 in paired rows coupled with pendimethalin application accrued weed biomass (10.7 g m−2) similar to the sequential application of pendimethalin and bispyribac-sodium coupled with uniform rows (8.1 g m−2). Similarly, IET-21214 with bispyribac-sodium application provided weed control similar to the sequential application of pendimethalin and bispyribac-sodium. Our study implied that grain yield of some cultivars could be improved by exploring their competitiveness through paired-row planting patterns with less use of herbicides.